Komunikasi Risiko Covid-19 dan Persiapan Menghadapi New Normal pada Masyarakat Kelurahan Air Putih Kota Pekanbaru - Suci Shinta Lestari; Muhammad Arif; Muhammad David Hendra; Muhammad Hanif Ahda; Nurul Mustaqimmah; Feriandri Utomo (MENARA RIAU, 2020)
Corona virus transmission is very fast. In a span of 2 months, this virus has spread to 28 countries, infected more than 40,000 people and killed more than 1,000 people in China. This has caused many people to panic so that they misunderstand information and are consumed by hoaxes. The application of risk communication that combines elements of speed and accuracy is very important in preventing transmission of the Corona virus. Where the social and economic impacts resulting from the dissemination of misinformation can be more severe than the spread of the virus itself. For this reason, this activity was carried out with the aim of controlling the chaos and information that developed in the community, so that it did not become a new disaster. Governments, research institutes and other authorities must be able to communicate science-based risks to foster public trust. The goal is so that the public can be more alert, prepare themselves, and reduce the impact caused by the Corona virus. Society needs explanation not only by bureaucrats, but also scientific explanation by experts. Scientists and governments must be present to fill in the information gaps. Because if it is not filled in, it can provide room for hoaxes to emerge. To get a perspective from the world of health, in the implementation of this activity the lecturers of the Communication Science study program collaborated with the lecturers of the Medicine study program at Abdurrab University Pekanbaru.